A Study of Musical Structure and Form of Hymn “Holy, Holy, Holy” in Kidung Jemaat No. 002 - Simamora, Mikhael Erikcon; Samosir, Tanesya Hotris (Sekolah Tinggi Teologi Abdiel, 2025)
The hymn “Holy, Holy, Holy” is one of the popular hymns in Kidung Jemaat, published by Yamuger Indonesia. This research aims to analyze the musical structure and form of the hymn, including the meaning of the lyrics, to understand its Biblical portion and its connection to the musical composition. This study uses qualitative research methods with a musicological and hermeneutic approach. Data collection was carried out through observation, documentation, and literature study. Data analysis follows the Miles & Huberman model, which consists of data display, data reduction, and conclusion drawing. The findings of this research are as follows: First, the musical analysis reveals that the hymn “Holy, Holy, Holy” has musical solid elements, including musical form, phrase or period, punctuation, motif, literal repetition, ascending sequence, diminution of interval, inversion, augmentation, cadence, and symmetry. Second, the meaning of the lyrics in this hymn expresses praise for God's majesty, sourced from Biblical verses in Isaiah 6:2-3, Psalm 5:4, Revelation 14:1-11, Psalm 18:12, 1 Timothy 6:16, Psalm 69:35, Psalm 103:22, and Psalm 145:10, and has a connection with the song's structure and form.